問題文全文(内容文):
◎次の等式を満たす$\vec{ x },$を$\vec{ a },\vec{ b }$を用いて表そう。
①$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + \vec{ y } = \vec{ a } \\
\vec{ x } + \vec{ y } = \vec{ b }
\end{array}
\right.
\end{eqnarray}$
②$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + 3\vec{ y } = \vec{ a } + \vec{ b }\\
\vec{ x } - \vec{ y } = \vec{ a }-\vec{ b }
\end{array}
\right.
\end{eqnarray}$
◎次の等式を満たす$\vec{ x },$を$\vec{ a },\vec{ b }$を用いて表そう。
①$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + \vec{ y } = \vec{ a } \\
\vec{ x } + \vec{ y } = \vec{ b }
\end{array}
\right.
\end{eqnarray}$
②$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + 3\vec{ y } = \vec{ a } + \vec{ b }\\
\vec{ x } - \vec{ y } = \vec{ a }-\vec{ b }
\end{array}
\right.
\end{eqnarray}$
単元:
Warning: usort() expects parameter 1 to be array, bool given in /home/kaiketsudb/kaiketsu-db.net/public_html/wp-content/themes/lightning-child-sample/single.php on line 102
Warning: Invalid argument supplied for foreach() in /home/kaiketsudb/kaiketsu-db.net/public_html/wp-content/themes/lightning-child-sample/single.php on line 103
Warning: usort() expects parameter 1 to be array, bool given in /home/kaiketsudb/kaiketsu-db.net/public_html/wp-content/themes/lightning-child-sample/single.php on line 102
Warning: Invalid argument supplied for foreach() in /home/kaiketsudb/kaiketsu-db.net/public_html/wp-content/themes/lightning-child-sample/single.php on line 103
指導講師:
とある男が授業をしてみた
問題文全文(内容文):
◎次の等式を満たす$\vec{ x },$を$\vec{ a },\vec{ b }$を用いて表そう。
①$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + \vec{ y } = \vec{ a } \\
\vec{ x } + \vec{ y } = \vec{ b }
\end{array}
\right.
\end{eqnarray}$
②$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + 3\vec{ y } = \vec{ a } + \vec{ b }\\
\vec{ x } - \vec{ y } = \vec{ a }-\vec{ b }
\end{array}
\right.
\end{eqnarray}$
◎次の等式を満たす$\vec{ x },$を$\vec{ a },\vec{ b }$を用いて表そう。
①$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + \vec{ y } = \vec{ a } \\
\vec{ x } + \vec{ y } = \vec{ b }
\end{array}
\right.
\end{eqnarray}$
②$\begin{eqnarray}
\left\{
\begin{array}{l}
2\vec{ x } + 3\vec{ y } = \vec{ a } + \vec{ b }\\
\vec{ x } - \vec{ y } = \vec{ a }-\vec{ b }
\end{array}
\right.
\end{eqnarray}$
投稿日:2015.11.21